Thermal Spin Transport Properties in Diarylethene-Based Molecule Devices - Gang Xu; Xingyi Tan; Dahua Ren (Advances in Condensed Matter Physics)
Spin caloritronic devices, as multifunctional devices, combining spintronics, and caloritronics, are essential for the sustainable development of humans. Here, a novel spin caloritronic device is presented using a diarylethene molecule photoswitch sandwiched among two semi-infinite zigzag graphene nanoribbons containing asymmetrical edge hydrogenation electrodes. We demonstrate that the temperature gradient between the right and the left electrodes can generate spin-up (SU) and spin-down (SD) currents moving in opposite orientations. Moreover, the mentioned currents possess approximately the same magnitudes, indicating a nearly nondissipative spin Seebeck effect. We also find that these currents are significantly dissimilar for the two photochromic isomers at different temperature gradients, demonstrating the excellent system’s switching nature. The obtained results reveal that the light can control the thermal spin transport properties.